The sociology of medical regulation an introduction - Chamberlain, John Martyn (Springer Netherlands, 2012)
This book provides a comprehensive examination of the complex issues surrounding the regulation of the medical profession. It offers up-to-date information on the current legislative framework and institutional arrangements surrounding the regulation in the United Kingdom. Well organized and written in an accessible way, it offers an insight into key sociological theories surrounding medical regulation. It gives a historically situated analysis of the contemporary relationship between medicine, the state and the public, and an overview of relevant social scientific research. Case studies highlight the practical or applied circumstances in which issues can occur. Readers will gain insight into possible future directions for medical governance.